Disease characteristics and clinical outcome over two decades from the Swiss pulmonary hypertension registry. (5th January 2022) - Appenzeller, Paula; Lichtblau, Mona; Berlier, Charlotte; Aubert, John‐David; Azzola, Andrea; Fellrath, Jean‐Marc; Geiser, Thomas; Lador, Frederic; Pohle, Susanne; Opitz, Isabelle; Schwerzmann, Markus; Stricker, Hans; et al.
Abstract: Pulmonary hypertension (PH), especially pulmonary arterial and chronic thromboembolic pulmonary hypertension (PAH/CTEPH), are rare and progressive conditions. Despite recent advances in treatment and prognosis, PH is still associated with impaired quality of life and survival. Long‐term PH‐registry data provide information on the changing PH‐epidemiology and may help to direct resources to patient's needs. This retrospective analysis of the Swiss Pulmonary Hypertension Registry includes patients newly diagnosed with PH (mainly PAH/CTEPH) registered from January 2001 to June 2019 at 13 Swiss hospitals. Patient characteristics (age, body mass index, gender, diagnosis), hemodynamics at baseline, treatment, days of follow‐up, and events (death, transplantation, pulmonary endarterectomy, or loss to follow‐up) at last visit were analyzed. Patients were stratified into four time periods according to their date of diagnosis. Survival was analyzed overall and separately for PAH/CTEPH and time periods. 1427 PH patients were included (thereof 560 PAH, 383 CTEPH). Over the years, age at baseline (mean ± SD) significantly increased from 59 ± 14 years in 2001–2005 to 66 ± 14 years in 2016–2019 ( p  < 0.001) while the gender distribution tended toward equality. Mean pulmonary artery pressure and pulmonary vascular resistance significantly decreased over time (from 46 ± 15 to 41 ± 11 mmHg, respectively, 9 ± 5 to 7 ± 4 WU, p  < 0.001). Three‐year survival substantially increased over consecutive periods from 69% to 91% (for PAH 63%–95%, for CTEPH 86%–93%) and was poorer in PAH than CTEPH independently of time period ( p  < 0.001). Most patients were treated with mono‐ or combination therapy and an increasing number of CTEPH underwent pulmonary endarterectomy (40% 2016–2019 vs. 15% 2001–2005). This long‐term PH registry reveals that over two decades of observation, newly diagnosed patients are older, less predominantly female, have less impaired hemodynamics and a better survival.